Cardiac Responses to Thermal, Physical, and Emotional Stress. Issue 5818 (8th July 1972) - Taggart, Peter; Parkinson, Peter; Carruthers, Malcolm
Abstract : We have studied the effect of a short period of exposure to the intense heat of a sauna bath on the electrocardiogram and plasma catecholamine, free fatty acid, and triglyceride concentrations in 17 subjects with apparently normal hearts and 18 persons with coronary heart disease. Similar observations were made on 11 of the 17 normal subjects and on 7 of the persons with coronary heart disease in response to exercise. Exposure to heat was associated with an increase in plasma adrenaline with no change in noradrenaline, free fatty acid, or triglyceride concentrations. Exercise was associated with the expected increase in both plasma noradrenaline and adrenaline concentrations. A heart rate up to 180 beats/min was observed in response to both heat and exercise. Apart from the ST-T changes inherent to sinus tachycardia, ST-T segment abnormalities were frequent in response to heat in both the subjects with normal and abnormal hearts, but little change occurred in the ST-T configuration when the subjects were exercised to produce comparable heart rates. Ectopic beats, sometimes numerous and multifocal, were observed in some subjects of both groups in response to heat, but not to exercise. It seems likely that the net unbalanced adrenaline component of the increased plasma catecholamine concentrations (which is also seen in certain emotional stress situations) is predominantly responsible for ischaemic-like manifestations of the electrocardiogram in susceptible subjects. The observations provide further validation for previously reported studies that it is the increased plasma noradrenaline in response to emotional stress that is associated with the release of free fatty acids and ultimate hypertriglyceridaemia, of probable importance in the aetiology of atheroma.